Pengaruh Motivasi dan Sikap Kerja Terhadap Disiplin Kerja Karyawan Pada PT Arashiyama Praya Kreasi - Sitta Nurhaliza (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to determine the effect of work motivation and work attitude on the work discipline of employees of PT Arashiyama Praya Kreasi. The method chosen in this study uses quantitative methods because quantitative research is used to examine certain populations or samples, data collection uses research instruments, data analysis is quantitative/statistical in nature, with the aim of testing predetermined hypotheses. The research population is all employees at PT Arashiyama Praya Kreasi numbered 120 employees. The research sample shows that the sampling method is 92 respondents. The results showed that work motivation and work attitude simultaneously had a positive and significant effect on work discipline at Arashiyama Praya Kreasi. This is because the discipline of employees in terms of additional work has been carried out properly. This research is suggested to carry out evaluations related to performance in order to motivate employees to work. Organizing events that can strengthen the working relationship between employees to be closer.